Glutamate receptor modulation and long-term synaptic plasticity - Collingridge, Graham (Henry Stewart Talks, 2011)
Synaptic plasticity, Long-term potentiation (LTP), Glutamate receptors, AMPA and NMDA receptors, Hippocampus, Learning & Memory, Phosphorylation